Carbon dioxide-Induced Corrosion of AISI 4140 Steel in Acidified Artificial Geothermal Brine - Anawati, Anawati; Izzat, Rayhan; Pragitta, Riene Kaelamanda; Hernandi, Rafli Ihsan (Makara Journal of Science, 2023)
Carbon dioxide (CO2)-induced corrosion often occurs in the structural materials of geothermal industry. The presence of CO2 influences the formation of various corrosion products. This research investigates the effect of dissolved CO2 in acidic brines on the corrosion behavior of AISI 4140 steel at atmospheric pressure. The brines were the standard brine, Ca-free brine, and high-salinity brine. The corrosion behavior was studied using electrochemical and immersion tests. A cyclic polarization test showed that the corrosion rate was higher in dissolved CO2 brine than in non-CO2 brine, and an immersion test demonstrated a similar result. In the absence of CO2, the presence of Ca ions in the brine reduced the corrosion rate of the alloy from 26.8 to 24.6 mmpy and further to 20.7 mmpy in the high-salinity brine. A similar trend was demonstrated during immersion in the CO2-containing brine, with higher rates of 37.1, 30.9, and 24.9 mmpy for the Ca-free, standard, and high-salinity brines, respectively. However, the Ca ions and high-salinity brines induced a more localized corrosion as pit and filiform. A surface analysis using an optical microscope revealed that immersion in CO2 brines generated 4–10-fold higher surface roughness than the non-CO2 brines. In all specimens, a protective layer was not established during the tests. No new phase was detected using X-Ray diffractometer after the immersion test. Moreover, no tendency of passivation was observed in the reverse scan of the cyclic polarization test.